Inovasi Pendidikan Islam Era 5.0: Membangun Generasi Cerdas dan Berkarakter - Rachman, Lutfi; Nurhanifansyah, Nurhanifansyah (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2024)
Islamic education plays an important role in shaping the character and intelligence of the younger generation. In the 5.0 era, the dominance of technology and artificial intelligence brings new challenges and opportunities for Islamic educational institutions to innovate. This study aims to explore the application of technology in Islamic education to build an intelligent and characterful generation. Using a qualitative method based on case studies, data were collected through in-depth interviews, observations, and document analysis in several Islamic educational institutions in major cities in Indonesia. The results of the study indicate that the use of technology, such as digital applications and collaborative platforms, increases student engagement, learning motivation, and character development. However, limited infrastructure in rural areas is an obstacle that requires special attention. This study contributes to offering innovative strategies for Islamic education in the digital era to create a superior generation that integrates academic and moral intelligence.